Maternal Outcomes Among Pregnant Women With Congenital Heart Disease–Associated Pulmonary Hypertension. Issue 7 (14th February 2023) - Zhang, Qian; Zhu, Fang; Shi, Guocheng; Hu, Chen; Zhang, Weituo; Huang, Puzhen; Zhu, Chunfeng; Gu, Hong; Yang, Dong; Li, Qiangqiang; Niu, Yonghua; Chen, Hao; et al.
Abstract : Background: Studies focused on pregnant women with congenital heart disease (CHD)–associated pulmonary hypertension (PH) are scarce and limited by small sample sizes and single-center design. This study sought to describe the pregnancy outcomes in women with CHD with and without PH. Methods: Outcomes for pregnant women with CHD were evaluated retrospectively from 1993 to 2016 and prospectively from 2017 to 2019 from 7 tertiary hospitals. PH was diagnosed on the basis of echocardiogram or catheterization. The incidence of maternal death, cardiac complications, and obstetric and offspring complications was compared for women with CHD and no PH, mild, and moderate-to-severe PH. Results: A total of 2220 pregnant women with CHD had completed pregnancies. PH associated with CHD was identified in 729 women, including 398 with mild PH (right ventricle to right atrium gradient 30–50 mm Hg) and 331 with moderate-to-severe PH (right ventricle to right atrium gradient >50 mm Hg). Maternal mortality occurred in 1 (0.1%), 0, and 19 (5.7%) women with CHD and no, mild, or moderate-to-severe PH, respectively. Of the 729 patients with PH, 619 (85%) had CHD-associated pulmonary arterial hypertension, and 110 (15%) had other forms of PH. Overall, patients with mild PH had better maternal outcomes than those with moderate-to-severe PH, including the incidence of maternal mortality or heart failure (7.8% versus 39.6%; P <0.001), other cardiac complications (9.0% versus 32.3%; P <0.001), and obstetric complications (5.3% versus 15.7%; P <0.001). Brain natriuretic peptide >100 ng/L (odds ratio, 1.9 [95% CI, 1.0–3.4], P =0.04) and New York Heart Association class III to IV (odds ratio, 2.9 [95% CI, 1.6–5.3], P <0.001) were independently associated with adverse maternal cardiac events in pregnancy with PH, whereas follow-up with a multidisciplinary team (odds ratio, 0.4 [95% CI, 0.2–0.6], P <0.001) and strict antenatal supervision (odds ratio, 0.5 [95% CI, 0.3–0.7], P =0.001) were protective. Conclusions: Women with CHD-associated mild PH appear to have better outcomes compared with women with CHD-associated moderate-to-severe PH, and with event rates similar for most outcomes with women with CHD and no PH. Multimodality risk assessment, including PH severity, brain natriuretic peptide level, and New York Heart Association class, may be useful in risk stratification in pregnancy with PH. Follow-up with a multidisciplinary team and strict antenatal supervision during pregnancy may also help to mitigate the risk of adverse maternal cardiac events.